Air abrasion device versus sandblasting device for surface pretreatment of CAD-CAM prosthetic materials - Nakajima, Kentaro; Ishida, Yoshiki; Miura, Daisuke; Hotta, Yasuhiro; Shinya, Akikazu (Japanese Society for Dental Materials and Devices, 2026)
This study evaluated the effects of various surface pretreatments using chairside air abrasion with water injection or laboratory sandblasting devices on the shear bond strength of resin luting agents to three CAD-CAM prosthetic materials: resin composites, glass ceramics, and zirconia. Pretreatments included air abrasion with water injection (29 µm or 53 µm alumina or bioactive glass powder), conventional sandblasting with 50 µm alumina, and hydrofluoric acid etching for glass ceramics. Specimens were prepared after embedding the blocks. Surface roughness was measured after pretreatment, and shear bond strength was tested following cementation. Failure modes were analyzed using an optical profilometer. Results showed that air abrasion with 50 µm alumina, whether using a chairside device with water injection or a laboratory sandblasting device, produced comparable bond strength. These findings suggest that chairside air abrasion with 50 µm alumina is a clinically viable alternative to laboratory sandblasting for surface treatment of CAD-CAM prosthetic materials.